Teriparatide treatment in non-uniting fracture: a case report - Kundu, Sujoy (International Journal of Research in Orthopaedics, 2017)
Impaired healing of fractures delays the rehabilitation process, which in turn impacts quality of life. The associated costs cause an economic burden to both the society and the patients. Till date, no systemic treatment is approved for fracture healing. Teriparatide is a synthetic polypeptide hormone consisting of the 1–34 fragment of human parathyroid hormone. Apart from its recognized indication of osteoporosis, there is a growing body of evidence suggesting its ability to accelerate fracture healing and heal non-unions. The purpose of this case report is to elucidate the Indian experience of 5 cases of use of Teriparatide for fracture healing - delayed unions and non-unions and in the setting of osteoporotic fracture. The primary observation of our case report depicts that teriparatide is a viable therapy not only to treat osteoporosis but also to accelerate fracture healing. Teriparatide therapy accelerates healing, which allows patients to return to normal life and work faster, optimizes medical resource utilization, reduces chances for future second surgery, requirement of bone graft and overall chronic morbidity associated with long-term treatment. The advantages of teriparatide therapy are that it can be prescribed in any types of fractures, including those that will be treated non-surgically; it can be commenced at any time, and can be applied through the entire healing period. Our observations are in line with other studies showing the effects of Teriparatide on delayed union and non-unions in human subjects.